Prevalence and Determinants of Wheezing and Bronchodilatation in Children With Cystic Fibrosis: A Retrospective Cohort Study - Galodé, Francois; Ladipo, O.; Andrieux, A.; Feghali, H.; Bui, S.; Fayon, Michael (Frontiers in Pediatrics, 2022)
Background Many patients with cystic fibrosis (CF) wheeze, and are dubbed as having CF-asthma. Understanding the determinants of such wheezing may avoid unnecessary treatments and open newer treatment avenues. Objectives Main: To evaluate the prevalence and characteristics of wheezing and a positive bronchodilatory response (BDR) in children with CF. Secondary: To identify the predictive markers and the impact of current wheezing a positive BDR. Methods A retrospective single-center study in children with CF. We determined the characteristics of physician-reported wheeze in patients <6 years, and a BDR in patients aged 6–17 years. Anthropometric, lung function, laboratory, genetic and microbiological data were recorded in all groups. Variables were compared using the Chi2 and Student t-tests, and ANOVA. Results 125 preschool and 69 school-aged children and adolescents with CF were included in the study. 71.2% of patients <6 years of age had had at least one episode of wheezing: 26.3% of patients were Transient Early Wheezers, 12.6% Late Onset Wheezers and 37.9% were Persistent Wheezers. The prevalence of a positive BDR was 73.5, 48.5, and 52.9% in the 6–8 years, 10–12 years, and 15–17 years age groups, respectively. Allergic factors were not predictive of wheezing in preschoolers. In the 6–8 years age group, the sum of wheal diameters of allergic skin prick tests (SPT, house dust mite + cat + dog dander) was greater in those with a BDR vs. no BDR (4 [2.0–8.8] vs. 1 [0–7.0] mm, p = 0.01). The presence of Pseudomonas aeruginosa in the bronchial secretions before 3 years of age was not significantly associated with either the presence of wheezing at the age of 6 years or a BDR in school-aged children and adolescents. The proportion of homozygous p.F508del patients was significantly lower in the group of patients who had wheezed by 6 years of age (60% vs. 72.7%, p = 0.009), but higher in the 6–8 years old group with a BDR vs. no BDR (64% vs. 36%, p = 0.04). Current wheezers at 6 years had a lower mean FEV1 vs. the non-current wheezers (91.5 ± 4.4% vs. 100.9 ± 2.4%; p = 0.047). Similarly, forced vital capacity (FVC) was significantly lower in the 6–8 years old group with BDR vs. no BDR (85 ± 19 vs. 101 ± 21%, p = 0.015). Conclusion Wheezing and BDR are very frequent findings in children with CF. Current wheeze at the age of 6 years was associated with worse lung function. Labeling wheezing in CF as “CF-Asthma” is misleading since the determinants are different, and may lead to inappropriate prescriptions of inhaled steroids.